Estimativas do balanço de energia e fluxo de carbono por diferentes métodos em floresta de transição no Sudoeste da Amazônia - Pereira, Osvaldo Alves (2013)
This study aimed to compare the energy balance and CO2 flux by Eddy Covariance (EC), Bowen ratio (RB) and modified Bowen ratio (MBR) systems in transitional forest between the Cerrado and the Amazon rainforest. The experiment was conducted in an area belonging to the Maracaí Farm, about 50 km northwest of the city of Sinop, Mato Grosso, Brazil. To consider the closure of the energy balance, the coefficient of determination R2 was used. CO2 fluxes (Fc), latent heat (LE) and sensible (H) through the statistical test Scheirer-Ray-Hare to detect possible differences between the flows of LE, H and Fc between seasons, methods, and interactions between method and season. The CO2 flux, estimated by the MBR, was tested as a function of the diffusion coefficients of turbulent sensible heat ( ) and latent heat ( ). H showed a significant difference between the RB and EC methods and between the wet and dry seasons (p-value < 0.001). Differences between the CO2 fluxes by EC and RBM methods depending on , ( ) were not significant between seasons and between methods (p > 0.05). In both methods, RB and EC, the net energy available prioritized LE flux even during the dry season. The energy balance for EC was underestimated by approximately 30% in the wet season and 5% in the dry season. The energy balance method RB closed at 100% during the dry season, but during the wet season was underestimated by 4%.